2016
DOI: 10.3109/17453674.2016.1170548
|View full text |Cite
|
Sign up to set email alerts
|

Similar patient-reported outcomes and performance after total knee arthroplasty with or without patellar resurfacing

Abstract: Background and purposeKnee pain after total knee arthroplasty (TKA) is not uncommon. Patellar retention in TKA is one cause of postoperative knee pain, and may lead to secondary addition of a patellar component. Patellar resurfacing in TKA is controversial. Its use ranges from 2% to 90% worldwide. In this randomized study, we compared the outcome after patellar resurfacing and after no resurfacing.Patients and methodsWe performed a prospective, randomized study of 74 patients with primary osteoarthritis who un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 35 publications
0
42
1
Order By: Relevance
“…No significant difference was detected in either clinical or radiological results between the two groups (14). Another study with medium followup period found patellar resurfacing had no advantage on knee function and patient satisfaction (15). No significant difference in functional outcome was detected between patellar resurfacing and retention in a randomised controlled trial including 1715 patients (16).…”
Section: Discussionmentioning
confidence: 93%
“…No significant difference was detected in either clinical or radiological results between the two groups (14). Another study with medium followup period found patellar resurfacing had no advantage on knee function and patient satisfaction (15). No significant difference in functional outcome was detected between patellar resurfacing and retention in a randomised controlled trial including 1715 patients (16).…”
Section: Discussionmentioning
confidence: 93%
“…However, these studies did not enrol patients who underwent TKA without patellar resurfacing. Although many studies have suggested there is no significant difference in functional outcomes between procedures that incorporated patellar resurfacing and that those that did not in TKA [13][14][15], the probability of AKP was higher in TKA procedures performed without patellar resurfacing than those in which it was [16]. Whether TKA without patellar resurfacing benefits from this femoral implant design modification with regard to AKP and patellar crepitus remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, 10% to 34% of TKA patients remain dissatisfied with their knee [1]. It has been reported that a large proportion of revision surgeries after TKA are due to instability [2]. Patient factors such as anatomical variations in bony anatomy and alignment and pathological changes in soft tissues can leave some patients more prone to instability than others.…”
mentioning
confidence: 99%